AFM-nanoSIMS correlative microscopy on multiphase elastomeric systems: Nanomechanical properties and elemental distribution at the nanoscale. (April 2023) - Cosas Fernandes, João P.; Federico, Carlos E.; Lentzen, Esther; Valle, Nathalie; Basterra-Beroiz, Beatriz; Weydert, Marc; Quintana, Robert
Abstract: The co-vulcanization of immiscible blends composed of two or more chemically different elastomers can lead to the formation of materials with uneven distribution of cross-links and different cross-linked structures. This is consequence of the competition between the vulcanization processes occurring in each phase. The solubility preferences of the vulcanization agents in each of the elastomers and the different rates they can be consumed in each phase are the main factors governing the phase-specific properties of these cured materials. To track the localization of curatives in immiscible elastomeric blends composed of polyisoprene (PI) and polybutadiene (BR), we combine atomic force microscopy (AFM) and high-resolution secondary ion mass spectrometry (nanoSIMS) imaging in co-localized analyses. The similar contrasts obtained allow for the superposition of topographic, nanomechanical and elemental chemical information in areas down to 5 × 5 μm 2 . Phase-specific properties can be directly correlated to the local sulfur content, reflecting the increasing cross-link density in each phase according to the vulcanization agents and amounts used. Results show that sulfur tends to be located in the BR phase of the blends and its local concentration can be enhanced by increasing the accelerator content, in accordance with estimations based on the Hansen solubility parameters. Graphical abstract: Image 1 Highlights: Correlative AFM-nanoSIMS was done in immiscible PI/BR blends in areas of 5 × 5 μm 2 . Direct correlation of phase-specific modulus, tan δ and sulfur content at nanoscale. Higher amount of sulfur in polybutadiene independently of sulfur/accelerator ratio. Sulfur content in BR phase is accentuated by the increase of the accelerator amount. HSP estimations for sulfur and accelerators suggest solubility preference towards BR.